Airway surface liquid pH is not acidic in children with cystic fibrosis - André Schultz (Nature Portfolio, 2017)
Modulation of airway surface liquid pH has been proposed as a therapy for cystic fibrosis, but whether pH is indeed altered in cystic fibrosis is controversial. Here, the authors develop a novel fibre-optic based pH measurement technology, and show that pH is not altered in children with cystic fibrosis.